164 Characterization and outcomes of spontaneous coronary artery dissection patients presenting with an acute coronary syndrome: insights from the ACALM registry. (May 2019) - Potluri, Rahul; Carter, Paul; Aziz, Amir; Vo, Minh; More, Ranjit; Sarma, Jaydeep; Ahmed, Asif; Adlam, David; Welsh, Robert; Bainey, Kevin
Abstract : Introduction: Spontaneous coronary artery dissection (SCAD) is recognised as an infrequent presentation of acute coronary syndromes (ACS). Using a large comprehensive UK ACS registry, we examined the incidence, demographic profile and long-term survival of ACS patients with SCAD. Methods: We compared ACS patients with SCAD versus without SCAD admitted to hospitals in the UK (England) between 2000 and 2014 from the Algorithm for Co-morbidity, Associations, Length of stay and Mortality (ACALM) registry (n=33, 163). ACALM uses a big data approach collecting ICD-10 and OPCS-4 coding systems to identify patient data. Primary outcome was all-cause mortality over a 14-year time period. Adjustment was performed using a Cox-regression model. Results: In our cohort, 182 patients (0.54%) were diagnosed with SCAD as the cause for ACS. Compared to patients without SCAD, patients with SCAD were younger, more commonly female and less likely to have traditional risk factors for ACS or significant comorbid conditions (Table 1 ). Revascularization with percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) surgery was uncommon with SCAD (11.0%, 2.7% respectively) compared to ACS patients without SCAD (50.7%, 10.6% respectively). All-cause mortality was significantly better in SCAD patients compared to non-SCAD ACS patients (10.4% vs. 32.1%, p=0.003). Kaplan-Meier curve comparing 5-year survival is shown below (figure 1 ). After adjusting for age, gender, ethnic group and the top causes of morbidity and mortality in the UK, patients with SCAD presenting as ACS demonstrate improved survival compared to ACS patients without SCAD (OR 1.89; 95% C.I 1.20–2.96). Conclusion: Accepting the potential of under reporting by clinicians in routine clinical practice, a minority of ACS patients in this large UK registry present with SCAD. These patients are commonly younger females without traditional risk factors for ACS. To our knowledge, this is the first study to demonstrate improved long-term survival over a 14-year period with SCAD. Additionally, our analysis suggests conservative therapy is safe in this patient population. Further studies are required to explore non-traditional risk factors, predictors of SCAD and best treatment strategy for these patients. Conflict of Interest: Nil